Analysis of gut microbiotal diversity in healthy young adults in Sunan County, Gansu Province, China - Ma, Yanqing; Ci, Caihong; Zhou, Yunsong; Zhang, Zilong; Gu, Qiaoling; Yang, Xiao; An, Fulong; An, Yan; Lan, Yongmei; Zhao, Jin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To examine gut microbiotal diversity in the Han Chinese and Yugur populations of Sunan County, Gansu Province, living in the same environmental conditions, and to analyze possible causes of differences in diversity. Methods: We selected 28 people, ages 18–45 years old, all of whom were third-generation pure Yugur or Han Chinese from Sunan County. Fresh fecal samples were collected, and total bacterial deoxyribonucleic acid (DNA) was extracted. We performed 16S ribosomal ribonucleic acid (16S rRNA) high-throughput sequencing (HTS) and bioinformatics to study the relationships among between gut microbiota structure, genetics, and dietary habits in Yugur and Han Chinese subjects. Results: We found 350 differential operational taxonomic units (OTUs) in Han Chinese and Yugur gut microbiota, proving that gut microbiota differed between the two populations. Gut microbes that were significantly more abundant in the Yugur than in the Han Chinese group included Bacteriodes, Ruminococcus, and Parasutterella; those that were less abundant among Yugurs than Han Chinese were Prevotella_9 and Escherichia. In addition, we found differences in predicted gut microbiota structural functions between the two populations. Conclusion: Yugur subjects demonstrated differences in gut microbiotal structure from Han Chinese subjects. This finding will provide a fundamental basis for further study of the relationships among gut microbiota, environmental factors, dietary factors, and disease in Sunan County.